Carmona retusa (Tsaang Gubat) as a potential oral antifungal agent - Bernardo, Mary Rose
Alternative to costly pharmaceutical drugs are in demand. One of the Sampung Halamang Gamot promoted by the Department of Health, Carmona refusa or more commonly known as Tsaang Gubat is said to have components with antifungal properties. The aim of this study is to test the antifungal property of different tsaang gubat plant part decoctions in different concentrations against Candida albicans and to compare it with Nystatin. The Disk Diffusion method was used where plates with Potato Dextrose Agar were streaked with Candida albicans. The zones of inhibition created by the filter paper disks soaked with tsaang gubat decoctions were recorded and analyzed. Statistical analysis using Two-way Analysis of Variance [P ≤ 0.05], One-way Analysis of Variance [P ≤ 0.05], Turkey and Least Significant Difference [P ≤ 0.05] was done. Based on the results, the study confirmed that Carmona retusa (tsaang gubat) leaves, stem and roots at 13%, 26% and 33% concentrations do not exhibit significant antifungal effect on Candida albicans.